Interactive Multimedia for Pancasila Education: Development and Feasibility Study in Primary Education - Wahyudi, Ilham; Kawuryan, Sekar Purbarini (Edunesia : Jurnal Ilmiah Pendidikan, 2025)
This study aims to develop interactive multimedia products suitable for educational use. The research method used is Research and Development (R&D) through ten stages, namely: (1) preliminary study; (2) planning; (3) initial product development; (4) initial field trial at SD Negeri Demangan with nine research subjects; (5) product revision; (6) main field trial at SD Negeri Giwangan with eighteen subjects; (7) product revision; (8) operational field trial at SD Negeri Jetisharjo with twenty-six subjects; (9) final revision; and (10) dissemination. The study results indicate that the interactive multimedia developed to enhance understanding of concepts and characters in Pancasila Education learning for grade 4 elementary schools is deemed suitable for use. The validation results from media and material experts place the product in the "very suitable" category. In the initial field trial, teachers gave the response "very suitable," while students gave the assessment "suitable." Furthermore, teachers and students assigned assessments to the "very suitable" category in both the main field trial and the operational field test. These findings indicate that the interactive multimedia effectively supports the Pancasila Education learning process and demonstrates the importance of integrating technology in modern classroom practices in elementary schools.